1972
DOI: 10.1113/jphysiol.1972.sp009956
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of palmitic, stearic and oleic acids in the sheep in the presence or absence of bile and/or pancreatic juice

Abstract: SUMMARY1. The absorption of 3H-and "IC-labelled palmitic, stearic and oleic acids under control conditions and in the absence of bile and/or pancreatic juice has been studied in sheep prepared with intestinal cannulae and reentrant fistulation of the thoracic lymph duct.2. Under control conditions the percentage recoveries in thoracic duct lymph of fatty acids introduced into the duodenum were: stearic acid 59-6 + 3-2 (mean + S.E. of mean), palmitic acid 71-1 + 1-2 and oleic acid 80'4+ 1*9.3. At the peak of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1973
1973
1985
1985

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…An important consideration in vivo will be the possible role of lysolecithin, the hydrolytic product of lecithin resulting from the action of Lecithinase A enzyme produced by the pancreas (Deuel, 1955). In a recent study Harrison & Leat (1972) stressed the importance of lysolecithin for fatty acid absorption in the sheep. However, in the rat, there is evidence that biliary lecithin, in contrast to lecithin from other sources, has special properties making it resistant to the action of pancreatic lecithinase (Boucrot, 1972).…”
Section: Possible Mechanism Ofaction Of Lecithinmentioning
confidence: 99%
“…An important consideration in vivo will be the possible role of lysolecithin, the hydrolytic product of lecithin resulting from the action of Lecithinase A enzyme produced by the pancreas (Deuel, 1955). In a recent study Harrison & Leat (1972) stressed the importance of lysolecithin for fatty acid absorption in the sheep. However, in the rat, there is evidence that biliary lecithin, in contrast to lecithin from other sources, has special properties making it resistant to the action of pancreatic lecithinase (Boucrot, 1972).…”
Section: Possible Mechanism Ofaction Of Lecithinmentioning
confidence: 99%
“…Because dietary lipids are hydrolysed in the rumen, the role of pancreatic juice in lipid absorption in the ruminant must be other than the hydrolysis of triglycerides. It has been suggested that pancreatic juice functions by converting biliary lecithin to lysolecithin which may be necessary for optimum solubility of fatty acids in the intestinal lumen [Leat and Harrison, 1969;Harrison and Leat, 1972]. However, it is possible that lysolecithin may function through its ability to enter the mucosal cell (in contrast to lecithin) where it would be esterified to form the lecithin necessary for synthesis of the chylomicron-very low density lipoprotein particle of sheep lymph.…”
Section: Origin and Formation Of Lymph Phospholipidsmentioning
confidence: 99%
“…All Harrison and Leat, 1972]. Two acids were studied simultaneously, 3H palmitic acid (100,uCi) with each of the 14C fatty acids (10 uCi) in turn.…”
Section: Surgical Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lennox et al (1968) reported the progressive disappearance of phospholipids through the intestine of sheep. Hydrolysed biliary phospholipids, together with bile salts, would help the micellar solubilization of fatty acids in sheep intestine and enhance the lipid absorption Harrison, 1969, 1974 ;Harrison and Leat, 1972 ;Lough and Smith, 1976). …”
mentioning
confidence: 99%